Geo Trio: Putting MapServer, KML, and Google Earth to work at the Province of British Columbia - Ross, Michael (FOSS4G,Open Source Geospatial Foundation (OSGeo), 2014)
Over the past four years, the Province of British Columbia has developed numerous web applications based on the powerful, template-driven output capabilities of UMN MapServer. By outputting custom KML that can be viewed in Google Earth, we have built an air-photo viewer that lets you display and print over 150 000 airphotos; a physical address viewer that lets you search for and display civic addresses in the context of road, property, and topography WMS layers; and a spatial reporting tool that dynamically generates a list of First Nations contacts that are appropriate for your current map view (pan and zoom and you automatically get a new report). We also built the FrontCounterBC Discovery Tool which combines all of the above viewers and adds tenure and interest layers for clients to determine potential conflicts with their proposed tenure and interest applications. All the above apps are simply KML NetworkLinks that make requests for KML against our UMN Mapserver Web Map Services.Come see how we do it and learn why MapServer has the most powerful KML support of any web mapping server.